Will the youth market revolutionise the marketing world? A call for research - CLAFFEY, ETHEL; Brady, Mairead (My University, 2006)
The emerging interactive marketplace, characterised by high levels of heterogeneity, is giving birth to a new type of technology savvy consumer. The advent of this new consumer would seem to be making traditional approaches to marketing redundant. Young adults, in particular, are early adopters of new technologies and the defining users of the digital media revolution. This paper describes key influences on the youth market?s buying behaviour in the face of emerging technologies and seeks to derive relevant implications for marketing managers targeting the youth sector.
PUBLISHED
Keywords: ICTs; Consumer Behaviour; Youth Market